2017
DOI: 10.1049/iet-wss.2016.0103
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of a hydroelectrically powered wireless sensor node for underground environmental monitoring

Abstract: This study describes a sensor node powered by an energy harvesting method based on the watermill principle. This method is suitable whenever a sensor node has to be deployed in the nearby of an underground water line, such as a drainage system or an aqueduct. The operating scenario for whom this solution has been developed and employed is a wireless sensor network for the monitoring of the environmental conditions of the so-called 'Bottini' in Siena, Italy. The 'Bottini' is a network of medieval aqueducts dug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…By monitoring the electricity consumption during six production processes of typical sewage discharge factories in the jurisdiction, it was found that the major production periods of large sewage discharge enterprises in November 2018 were concentrated in the following four sections: [4][5][6][7][8][9][10][11][12], [15][16][17][18][19][20][21][22][23], [24][25] and [27][28][29][30]. This performance was consistent with the time section when the concentration of pollution factors was increased in our urban environmental information monitoring analysis.…”
Section: Resultssupporting
confidence: 72%
“…By monitoring the electricity consumption during six production processes of typical sewage discharge factories in the jurisdiction, it was found that the major production periods of large sewage discharge enterprises in November 2018 were concentrated in the following four sections: [4][5][6][7][8][9][10][11][12], [15][16][17][18][19][20][21][22][23], [24][25] and [27][28][29][30]. This performance was consistent with the time section when the concentration of pollution factors was increased in our urban environmental information monitoring analysis.…”
Section: Resultssupporting
confidence: 72%
“…In general, the most immediate energy-saving strategy obviously is to provide the sensor node with an energy harvesting solution [ 18 ]: the most common is the use of photovoltaic panels [ 19 ] but also other strategies have been proposed [ 20 , 21 ]. An hydroelectrically powered sensor node was already discussed by the authors in [ 22 ]. While all these solutions are able to continuously power the monitoring system, they are unsustainable in term of costs.…”
Section: Related Workmentioning
confidence: 99%
“…Indeed, common energy-harvesting solutions like solar cells and wind turbines are useless due to the lack of the primary source of energy (i.e., the sun light and/or the wind). Hence, some recent works have investigated the possibility of deploying alternative energy-harvesting solutions [1,2]. However, off-the-shelf devices that incorporate these mechanisms are still difficult to be found.…”
Section: Introductionmentioning
confidence: 99%